First record of Tetranychus ludeni Zacher (Acariformes: Tetranychidae) in Italy. Issue 1 (17th February 2019) - Ragusa, Ernesto; Sinacori, Milko; Tsolakis, Haralabos
ABSTRACT: Tetranychus ludeni Zacher is reported here for the first time in Italy. It was found on some cultivated and spontaneous plants, often associated with Tetranychus urticae Koch. Four phytoseiid mites, widely distributed in the Mediterranean countries, Phytoseiulus persimilis Athias-Henriot, Iphiseius degenerans Berlese, Typhlodromus ( Anthoseius ) kerkirae Swirski and Ragusa, and Typhlodromus ( Anthoseius ) transvaalensis Nesbitt, were found associated with T. ludeni In Sicily. The morphological characters for the identification of the four Italian Tetranychus species are also reported.